First time and repeat caucasian visitors to Singapore. - Chong, Yoke Ting. (2008)
This applied research project investigates the differences between first time and repeat Caucasian tourists. It examines their satisfaction with Singapore as a holiday destination and reports on the findings of their perceptions of destination attributes. Their future holiday intentions to return to Singapore are also investigated.